Effect of Leaf Positions on Total Phenolics, Flavonoids and Proanthocyanidins Content and Antioxidant Activities in Lantana Camara (L) (Journal of Scientific Research, 2009)
Changes in the level of phenolics, flavonoids and proanthocyanidins with leaf positions were studied in L. camara twigs. Leaves at different positions (from apex to base) in a twig represented gradient increase in the leaf age, apical being the youngest leaves. The study showed that the fresh weight, dry weight and area of the leaves increased rapidly from I until IV position in a twig. Levels of phenolics remained unchanged from I to V leaf position, while a sharp increase in the levels of proanthocyanidins and flavonoids was observed during I to III leaf position which decreased markedly thereafter. At any leaf position in a twig, the level of proanthocynidin was higher than both phenolics and flavonoids, while the proportion of flavonoids was much higher than the phenolics. In fact, phenolics were present in very small amounts. In addition, antioxidant potential of leaves extracts was measured in terms of reducing and scavenging activity. The study revealed that extracts prepared from leaves present from I to III position exhibited significantly higher antioxidant activities than the leaves present from IV to V position. The study thus revealed that leaf positions (age) influence the level of secondary metabolites and thereby their antioxidant properties. Keywords: Antioxidant; Flavonoids; Lantana camara; Phenolics; Proanthocynidins.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i2.1873